2016
DOI: 10.5812/ircmj.25390
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence of Burnout Syndrome and Associated Factors Among Rural Health Workers (Behvarzes) in South Khorasan

Abstract: BackgroundEssential primary health care is delivered through the public health center PHC network by public health workers (Behvarzs). Health workers are exposed to different types of stresses while working.ObjectivesThe aim of this study is to determine the prevalence of burnout and associated factors among rural health workers in the health centers of Birjand University of Medical Sciences.Patients and MethodsAll rural health workers of health centers under the coverage of the Birjand University of Medical S… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
19
2

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 25 publications
(27 citation statements)
references
References 15 publications
4
19
2
Order By: Relevance
“…It was also found from this current study (Table 6) that older people between 41 and 50 years were more vulnerable to burnouts than the other age groups. This is in agreement with the work done by Bijari and Abassi [33], where they found that that older health workers aged 40-50 have a greater subjection to psychological and physical oppressions caused by fatigue resulting from overworking and carrying out tedious duties. Irrespective of the health worker group, it was revealed from this study that the higher the working experience, the more likely it is for any health professional to encounter burnouts.…”
Section: Discussionsupporting
confidence: 92%
“…It was also found from this current study (Table 6) that older people between 41 and 50 years were more vulnerable to burnouts than the other age groups. This is in agreement with the work done by Bijari and Abassi [33], where they found that that older health workers aged 40-50 have a greater subjection to psychological and physical oppressions caused by fatigue resulting from overworking and carrying out tedious duties. Irrespective of the health worker group, it was revealed from this study that the higher the working experience, the more likely it is for any health professional to encounter burnouts.…”
Section: Discussionsupporting
confidence: 92%
“…The findings are consistent with the conclusions in some of the previous small-scale studies conducted in township hospitals in China [18,20,27,45]. 28.8% of the rural health workers in South Khorasan reported moderate burnout and 5.7% were in severe burnout [19], and these two proportions were 15.5% and 1.1% respectively among rural primary healthcare workers in Iran [17]. It should be noticed that the degree of job burnout among the rural primary healthcare workers in China was much higher.…”
Section: Prevalence Of Burnout Among Rural Health Workerssupporting
confidence: 92%
“…Moreover, compared to the health professionals in the general hospitals, the health workers in the primary healthcare system are facing relatively less work resource, lower wages and less career development opportunities, especially in rural areas [15], which may also increase their perceived job stress [14,18]. Previous studies revealed that the majority of rural health workers are experiencing moderate burnout, and the common predictors included education level, years of employment, workload, and so on [14,[18][19][20]. In China, the expanding duties of public health service provision [21], the new challenges merged from the health system reform [22][23][24], altogether with the long-lasting shortage of health workforce [25,26] are increasing the risks of job burnout among the health workers in the rural primary care system.…”
Section: Introductionmentioning
confidence: 99%
“…If the scores in three dimensions were all low, then respondents exhibited low burnout levels. Other conditions in the three dimensions were considered as middle‐level burnout (Bijari & Abassi, ; Maslach & Jackson., ). The Cronbach's alpha coefficient and average variance extracted (AVE) were 0.727 and 0.667, respectively.…”
Section: Methodsmentioning
confidence: 99%
“…Therefore, education level could influence on burnout of public health workers at city level, but it may not affect the burnout of township workers. In terms of work‐related factors, daily working time, income and interpersonal relationship have been proved to be important factors affecting job burnout (Bijari & Abassi, ; Liu et al, ; West et al, ; Zhang et al, ). With regard to income level, public health institutions have ceased charging for service administrative undertakings in 2017 (Zhu, Lu, Cheng, & Zhou, ).…”
Section: Introductionmentioning
confidence: 99%